When lawns become forests - Fänge, Elin (2021)
For a long time, lawns have dominated urban areas but are they good for human health and well-being? This study investigates how natural/forest-like vegetation affects human health and well-being and discusses why static lawns still dominate areas today even though there is much research on the positive benefits of natural/forest-like vegetation. The study has three main methods; 1 - A literature study that looks into what Swedish state-owned organizations, global organization, and research studies write on the subject of human health and well-being connected to human visits in natural/forest-like vegetation. 2 - A observational study conducted in a town of Viken, Scania, Sweden looking what inhabitants do in a forest compared to a lawn. Also, a bird recording was done to count how many birds sing in the areas of the forest and lawn. 3 - An ArcGIS, Service Area analysis was done to calculate how many inhabitants today have access to the forest and lawn areas in the district of Svanebäck, Viken. The results present a compelling argument for why decisionmakers need to start looking into changing existing lawn areas to natural/forest-like vegetation. This study also presents the consequences of not having daily access to natural/forest-like vegetation.